Pardon for Corruptors: An Examination of Repentance and Restitution in Islamic Criminal Law - Nasution, Liantha Adam; Nasution, Fatimah Islamy; Siti Aminah; Zulfahmi , Zulfahmi (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the granting of clemency to perpetrators of corruption who return assets from the perspective of positive law and Islamic criminal law. This study examines the definition, elements, and mechanisms for handling corruption based on Law No. 31 of 1999 jo. Law No. 20 of 2001, Law No. 22 of 2002, and discusses the concept of jarimah ghulul in Islamic law, which emphasizes sincere repentance and restitution as prerequisites for divine forgiveness. The method used in this study is legal-normative and literature review to compare national legal norms with the principles of maqashid syariah, with a focus on maintaining justice, deterrence, and prevention of criminal acts. The novelty of this research lies in the fact that sincere repentance accompanied by restitution is an essential element for obtaining divine forgiveness, without neglecting the function of ta'zir punishment as a deterrent to prevent the repetition of the same act. The results of the study indicate that although clemency in positive law can be seen as a humane step toward the rehabilitation of offenders, its application must be accompanied by the condition of full asset restitution and a thorough evaluation of the socio-economic impact. This study provides recommendations for reforming pardon policies and integrating Islamic legal principles into regulations governing the restitution of corrupt officials' assets, with the aim of supporting comprehensive, fair, and effective anti-corruption efforts. These conclusions are expected to serve as a reference for policymakers and legal practitioners in formulating pardon mechanisms that not only prioritize humanitarian aspects but also uphold justice and prevent the recurrence of similar criminal acts.